Freshwater copepods in the tributaries of the lower Mekong River Basin in Thailand - KAMONWAN KOOMPOOT; SANTI WATIROYRAM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Koompoot K, Watiroyram S. 2025. Freshwater copepods in the tributaries of the lower Mekong River Basin in Thailand. Biodiversitas 26: 1846-1859. The study of copepod species diversity exclusively in the Mekong River Basin of Thailand has been sporadic, with no relevant publications for over a decade. Additionally, cyclopoid taxonomy remains a serious issue. This study investigated the species composition and distribution of copepods in three river basins of the Mekong River in Thailand: the Mekong, Songkhram, and Mun River Basins. Samples were qualitatively collected using a 60-µm plankton net during the monsoon rainy season by dragging the net from the limnetic zone to the littoral zone. A total of 47 species were identified from 480 samples collected across various waterbodies between 2020 and 2023 in seven provinces within the Mekong River Watershed, including Nong Khai, Bueng Kan, Udon Thani, Sakon Nakhon, Nakhon Phanom, Amnat Charoen, and Ubon Ratchathani. Among 27 calanoid and 20 cyclopoid species, one new cyclopoid species was named and published in prior research, and one new calanoid species is currently being prepared for the nomenclature process. Two cyclopoid copepod species were newly recorded in Thailand: Mesocyclops woutersi and Microcyclops pachyspina. We confirmed the presence of Microcyclops karvei in the country after its previous status had been uncertain. Furthermore, at least three calanoid species previously recorded in the study area: Mongolodiaptomus uenoi, Neodiaptomus songkhramensis, and Phyllodiaptomus christineae were not observed, suggesting their rarity, potential disappearance, or possible taxonomic misidentification. Similar to cyclopoid copepods, additional sampling and taxonomic study are required for confirmation. The species diversity and species list have been updated, and a brief morphological description along with taxonomic notes are provided for the two newly recorded species and one rare species of cyclopoid copepods.